A holistic approach to collection security implementation in university libraries - Maidabino, A.A.; Zainab, A.N. (2012)
This study proposed the "house model" to construct an instrument to assess collection security implementation in university libraries. The factors and items are extracted from published literature on library security and library collection security issues. The instrument comprises five factors: collection security governance; operations and processes; people issues; physical and technical aspects of collection security and the security culture in the libraries. The instrument was tested on 61 senior and professional librarians from four Nigerian universities. Reliability tests indicate that all factors are relevant with Cronbach's alpha value of above 0.7 suggesting the reliability of the instrument for use in a wider sample. Published by Elsevier Ltd.